Metal allergy after the Nuss procedure for pectus excavatum: a review - Gałązka, Przemysław; Leis, Kamil; Kroczek, Kacper; Baska, Aleksandra; Kazik, Jakub; Czajkowski, Rafał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Minimally invasive repair of pectus excavatum (MIRPE) technique (the Nuss procedure) is a minimally-invasive method that is commonly used in the treatment of pectus excavatum. An allergic reaction to the metal alloy bar that is implanted in the thorax during the procedure is a reported complication. We briefly review current literature concerning epidemiology, mechanisms and research results of allergic reactions after Nuss bar implantation. This allergic reaction occurs in approximately 2.7% of patients and is caused by metals used in the medical implant. The most common symptoms include fever and skin lesions such as allergic dermatitis. Elevated levels of C-reactive protein is a frequent finding in laboratory tests. In order to minimize the risk of such complications, taking a detailed allergy-based medical history and conducting allergy tests, i.e. patch test are required. Allergic reactions can be managed with conservative treatment such as general or topical glucocorticosteroid therapy and antihistamine agents. Severe allergic reactions can be addressed by implant revision, replacement of the steel bar with a titanium substitute or removal of the stabilization at all. Although the risk of an allergic reaction to titanium is smaller it still exists, the titanium substitute is not routinely used due to its higher cost and lesser plasticity which has a negative impact on matching a stabilizing bar during the surgery. Surgeons treating pectus excavatum should remember about the possible allergic reactions after implantation of the metal bar and be familiar with methods of diagnosis and treatment of those complications.